Potential confounding factors in measurement of specific cell‐free seminal mRNAs and microRNAs derived from human reproductive organs. (1st July 2016) - Dong, T. T.; Yu, Q.; Qing, X. R.; Ma, X. L.; Dong, W. W.; Shi, J.; Li, H. G.
Summary: Cell‐free seminal RNA (cfs‐RNA) is mixed transcripts derived from male reproductive organs, and is potential biomarker for the research and diagnosis of male reproductive‐related diseases. However, some clinical factors, including age, asymptomatic Ureaplasma urealyticum (UU) infection, scrotal heat stress, abstinence period, and the storage condition of semen samples, may interfere with sperm parameters and the measurement of seminal biomarkers. Accordingly, this study was designed to evaluate the effect of above clinical factors on the measurement of cfs‐RNA, aiming to lay a foundation for its research use and potential clinical application. Semen samples were collected according to the selected clinical factors. Cell‐free seminal plasma was obtained by centrifugation and total RNA was extracted with TRIzol LS. Selective male reproductive organ‐specific cfs‐mRNAs and cfs‐miRNAs were quantified by quantitative real‐time PCR. The concentration and total amount of cfs‐mRNAs and cfs‐miRNAs in one ejaculate were calculated and compared. ACTB, DDX4 (testis‐specific), WFDC9 (epididymis‐specific), and miR‐514a‐3p (testis‐specific) significantly increased after scrotal heat stress. SEMG1 (seminal vesicle‐specific) showed declining tendency with the prolonged abstinence period. Age, asymptomatic UU infection, and the storage condition showed no significant impact on the measurement of cfs‐RNA. These results indicate that scrotal heat stress significantly interfere with the selected cfs‐RNA derived from the testis and epididymis, and abstinence period may affect the yield of cfs‐mRNA from seminal vesicle, while other clinical factors has no significant impact on the measurement. Thus, heat exposure and abstinence period should be considered for the cfs‐RNA measurement in its research or clinical application.